2022
DOI: 10.1136/jitc-2021-004080
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and predictive biomarkers of immunotherapy in Epstein-Barr virus-associated gastric cancer

Abstract: BackgroundEpstein-Barr virus (EBV)-associated gastric cancer (GC) (EBVaGC) is a distinct molecular subtype of GC with a favorable prognosis. However, the exact effects and potential mechanisms of EBV infection on immune checkpoint blockade (ICB) efficacy in GC remain to be clarified. Additionally, EBV-encoded RNA (EBER) in situ hybridization (ISH), the traditional method to detect EBV, could cause false-positive/false-negative results and not allow for characterizing other molecular biomarkers recommended by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 53 publications
(49 reference statements)
2
23
0
Order By: Relevance
“…In another small PD-1 treatment GC cohort in Japan, the ORR was 33% [ 43 ]. Recently, Bai and colleagues also found EBV+/pMMR could achieve a high ORR and had better survival than EBV-/pMMR patients with GC [ 44 ]. Therefore, these findings suggest that EBV+ GC is an “immune hot” subtype and could benefit from PD-1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In another small PD-1 treatment GC cohort in Japan, the ORR was 33% [ 43 ]. Recently, Bai and colleagues also found EBV+/pMMR could achieve a high ORR and had better survival than EBV-/pMMR patients with GC [ 44 ]. Therefore, these findings suggest that EBV+ GC is an “immune hot” subtype and could benefit from PD-1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whether TMB can be used as an independent predictor of anti-PD-1 therapy requires further investigation. Previous studies have indicated that EBV positivity in the tumor is associated with a response to the PD-1 antibody [ 33 ]. However, in the present study, EBV status was not associated with ORR and PFS in SRCC.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective observational study showed that 3 of 9 patients with EBV-positive GC treated with ICIs achieved partial response after immunotherapy, with a longest duration of response of 18 months [ 57 ]. Furthermore, through next-generation sequencing-based detection of EBV infection, patients with EBV-positive GC showed a better response to immunotherapy than those with EBV-negative GC [ 58 ]. Thus, EBV positivity is a potential predictive biomarker for immunotherapy response in GC.…”
Section: Biomarkers For Gc Immunotherapymentioning
confidence: 99%